Verbal Interactions in Online Education: Challenges and Strategies - BELLILET, Ouided (Journal of Human Sciences, 2025)
Teaching has transitioned from in-person to e-Learning. Face-to-face communication now takes place through telecommunication, thanks to Web 2.0 technology. Virtual interaction, whether synchronous or asynchronous, mediated by a keyboard and facilitated through an internet connection, now largely dominates teaching and training platforms. Speech acts are guided by conversational and conventional factors such as context, the participatory (collaborative) framework, the intent of the exchange, and interpersonal relationships. In verbal interactions, whether oral or written in the context of computer-mediated communication, the specific features of the connection tools, the innovative context of the discussion, and their impact on the didactic approach to training and its educational effectiveness are crucial. The goal is to study how participants manage the enunciation situation and co-construct meaning in a digital environment shaped by civility, reflecting the sociocultural parameter.